Investigating the impact of adventure education on children's physical, cognitive and socio-emotional development: A mixed method systematic review. - Ruhina Binta A Ghani; Patrick W C Lau; Nike Lu; Peng Zhou; Jing Jing Wang (PLoS ONE)
This mixed-method systematic review examines how Adventure Education is perceived by children and its impact on their development. Children's age ranged between 06-18 years. AE been reported to improve participants' leadership, self-efficacy, peer support, relationship skills, independence, and the ability to follow instructions. Six quantitative research studies have shown a positive association of AE with various socio-emotional development outcomes. Participants exhibited enhanced resilience, hedonic balance, and life satisfaction. Individuals engaged in AE were found to experience reduced mental health issues and stress levels. One study found that the AE program significantly impacted physical activity outcomes, with effect sizes ranging from 0.029 to 0.663. However, long-term effects could not be definitively concluded due to the lack of follow-up measures of the interventions.